The strong goldbach conjecture and the function g(n): An analysis of prime distribution (Research, Society and Development, 2025)
Goldbach's Conjecture, an ancient and important problem in number theory, states that every even number greater than 2 can be expressed as the sum of two prime numbers. Although many advances have been made in the search for a solution to this conjecture, it remains unsolved to this day. The goal of the article is to analyze the relationship between Goldbach's Conjecture and the distribution of prime numbers, two fundamental questions in number theory. The main results and theories used by mathematicians to try to solve the conjecture will be presented, as well as discussing how the study of prime number distribution can lead to significant advances in this search. The importance of the research lies in solving one of the greatest mysteries in mathematics, as well as in the implications of the conjecture in other areas of science and technology. Additionally, the research contributes to the advancement of number theory and the understanding of prime number distribution, a fundamental problem in mathematics.